2023
DOI: 10.4018/978-1-6684-6607-0.ch005
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mobile Devices on the Travel Behavior of Millennials (Gen Y)

Abstract: The purpose of this chapter is to explore the use of mobile devices (i.e., smartphones, smartwatches, tablets) by Generation Y (Millennials), in the three phases of travel (pre-trip, on-site, post-trip). In order to meet this purpose, a survey was conducted via a structured self-completed questionnaire in a sample of 211 Millennials in Greece. The study's results revealed that Millennials are heavy users of the internet and social media to which they connect daily and spend several hours of the day. Mobile dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…One of the earlier studies supporting this hypothesis is the research conducted by Husin (2023), Nurfauzi et al, (2023), Trihas et al, (2023. In their research, they found that guests who perceive the price of a product to be in line with the value they receive are more likely to give positive reviews about the product via eWOM.…”
Section: Price and Electronic Word Of Mouthmentioning
confidence: 88%
“…One of the earlier studies supporting this hypothesis is the research conducted by Husin (2023), Nurfauzi et al, (2023), Trihas et al, (2023. In their research, they found that guests who perceive the price of a product to be in line with the value they receive are more likely to give positive reviews about the product via eWOM.…”
Section: Price and Electronic Word Of Mouthmentioning
confidence: 88%